2019
DOI: 10.3389/fpls.2019.00659
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Light/Dark Cycle on Photosynthetic Pathway Switching and CO2 Absorption in Two Dendrobium Species

Abstract: Many Dendrobium species are both ornamental and medicinal plants in China. Several wild species have been exploited to near extinction, and facility cultivation has become an important way to meet the great market demand. Most Dendrobium species have evolved into crassulacean acid metabolism (CAM) pathways in adapting to harsh epiphytic environment, leading to low daily net CO 2 absorption. Photosynthetic pathways of many facultative CAM plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…To combat daytime water loss, some C 3 plants evolved the CAM pathway. Dendrobium is a perennial semi-shade herb, and some varieties are facultative CAM plants ( Cheng et al, 2019 ; Li et al, 2019 ). In nocturnal cells, phosphoenolpyruvate (PEP) works as a CO 2 acceptor, which is catalyzed by PEP carboxylase to generate oxaloacetate.…”
Section: Discussionmentioning
confidence: 99%
“…To combat daytime water loss, some C 3 plants evolved the CAM pathway. Dendrobium is a perennial semi-shade herb, and some varieties are facultative CAM plants ( Cheng et al, 2019 ; Li et al, 2019 ). In nocturnal cells, phosphoenolpyruvate (PEP) works as a CO 2 acceptor, which is catalyzed by PEP carboxylase to generate oxaloacetate.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the categories and contents of volatile compounds in D. officinale from different regions were different, with the samples from Zhejiang Province (ZB1 and ZB2) containing the most, and those from Fujian Province (FB1 and FB2) the least (Table 1). Cheng [16] found that short light/dark cycle can increase the biomass and polysaccharide yield of D. officinale. Different growth condition and symbiotic bacteria in the roots of D. officinale may also lead to differences in volatile components [17], so the categories and contents of volatile compounds in D. officinale from different regions may be caused by the different temperature, humidity, soil conditions or sunshine duration in the different regions.…”
Section: Discussionmentioning
confidence: 99%
“…Nutrient solution was sprayed to the roots one time per hour and 10 seconds for each time. The formula of nutrient solution for aeroponic cultivation was followed by Cheng et al [12] EC and pH of the nutrient solution were controlled at 0.6-0.7 ms/cm and 6.0-6.5, respectively.…”
Section: Experimental Materials and Cultivation Conditionsmentioning
confidence: 99%
“…The higher light net CO 2 exchange amounts during short light/dark cycles might be related to stomatal movement, leaf thickness, and leaf anatomical structure. This was due to the fact that the short light/dark cycles could induce the higher stomatal conductances of D. officinale in light period [12] . Structure features of leaf might affect CO 2 concentration in chloroplast stroma [24] , thus affecting the photosynthetic capacity of D. officinale.…”
Section: Effects Of Short Light/dark Cycles On Photosynthetic Electromentioning
confidence: 99%
See 1 more Smart Citation